Inquiring into the Coloniality of Knowledge, Power, and Being in EFL Textbooks - Astrid Núñez-Pardo (Asociación Colombiana de Profesores de Ingles, 2020)
This article inquires into the coloniality present in EFL textbooks, which continue being used as the core resource for language learning and teaching in Colombia. However, its instrumentalization, imperialism, and exploitation as an instrument of subalternation suggest that EFL textbooks produced by foreign and local publishing houses in the Colombian context are colonised in three interrelated dimensions: knowledge, power, and being. Therefore, this research proposal aims at unveiling the ontological, epistemological, and power criteria rooted in critical interculturality as a decolonial alternative, and inspired by the decolonial turn, to orient the development of other contextualised materials from the voices of Colombian teachers, authors and experts.